Desarrollo de las competencias lingüística y digital a través de la creación de revistas on-line en 4º de la ESO - Montañés Laurenz, Garikoitz (Huarte de San Juan. Filología y Didáctica de la Lengua, 2014)
This sequence includes the preparation, during a 4th of ESO school year, of digital magazines in groups of three students. The project appears as a result of the study and analysis of the reading comprehension in different formats. Taking this into account, the work comprehends three parts: one focused on stories and reports; another one, on interviews and the last one; on editorials. Each group will choose the topic, the design and the contents of their magazine, a task that will allow them to im-prove, among others, their linguistics and digital competences. The key is that students will learn to identify and reproduce the basic characteristics of journalism, its different genres and their various perspectives. This is why this sequence always uses real examples, in order to prepare the students to handle todays’ overexposure to information, in a social network blatantly influenced by the Internet.